Copper Metallization of Gold Nanostructure Activated Polypyrrole by Electroless Deposition. (20th August 2017) - Pandey, Richa; Jian, Nan; Inberg, Alexandra; Palmer, Richard E.; Shacham-Diamand, Yosi
Abstract: We report on the study of novel polymeric electrodes made by the selective, electroless plating, of Copper (Cu) films on gold (Au) nanostructure-modified polypyrrole (Ppy). The main aim of the work is to define the effect of Au nanoparticle seed preparation method on its catalytic properties for Cu electroless deposition. The Au nanostructures were produced by two different techniques, namely, cluster beam deposition from a magnetron sputtering/gas condensation source (with precise size and composition control) and electrochemical deposition. To carry out the research, polypyrrole films were first synthesized by electro-polymerization on Au (200 nm)/SiO2 /Si substrates, followed by modification of the polymer surface by either electroplating of Au nanoparticles or Au923 clusters deposition from a magnetron cluster source. The gold nanoparticle modified electrodes were subjected to copper electroless deposition for different time intervals. The morphology, growth and nucleation kinetics of the resulting copper film were studied by environmental scanning electron microscopy-Energy dispersive X-ray spectroscopy (ESEM-EDS), atomic force microscopy (AFM) and X-ray fluorescence (XRF). Although both nanoparticle type showed similar incubation time, a faster catalytic response, once deposition had been initiated, was observed when the polypyrrole film was modified with Au923 clusters. The incubation time was independent of cluster size and type. This could be explained by a simple model assuming that the incubation time depends on similar parameters for both nanoparticle types, such as metal-metal (Au-Cu) binding energy, crystallographic misfit (Au- Cu) and lateral growth of the copper film. Further discussion is presented in this paper in attempt to explain the different growth rate of Cu film catalysed by the Au923 clusters and electroplated Au nanoparticles.